Tissue mimicking materials for imaging and therapy phantoms: a review. (16th December 2020) - McGarry, Conor K; Grattan, Lesley J; Ivory, Aoife M; Leek, Francesca; Liney, Gary P; Liu, Yang; Miloro, Piero; Rai, Robba; Robinson, Andrew P; Shih, Albert J; Zeqiri, Bajram; Clark, Catharine H
Abstract: Tissue mimicking materials (TMMs), typically contained within phantoms, have been used for many decades in both imaging and therapeutic applications. This review investigates the specifications that are typically being used in development of the latest TMMs. The imaging modalities that have been investigated focus around CT, mammography, SPECT, PET, MRI and ultrasound. Therapeutic applications discussed within the review include radiotherapy, thermal therapy and surgical applications. A number of modalities were not reviewed including optical spectroscopy, optical imaging and planar x-rays. The emergence of image guided interventions and multimodality imaging have placed an increasing demand on the number of specifications on the latest TMMs. Material specification standards are available in some imaging areas such as ultrasound. It is recommended that this should be replicated for other imaging and therapeutic modalities. Materials used within phantoms have been reviewed for a series of imaging and therapeutic applications with the potential to become a testbed for cross-fertilization of materials across modalities. Deformation, texture, multimodality imaging and perfusion are common themes that are currently under development.